Internal Combustion Engine Coolant Jacket design guidelines study with 3D CHT-CFD - Johansson, Andreas (My University, 2019)
High thermal loads lead to high demands on the engine cooling system. When analysing the heat transfer within the engine, from the combustion/exhaust gases to the coolant, CFD and FE has historically been performed separately for the coolant and solid regions. When the heat loads become more complex, the coolant jacket design does as well. Thus it is important to analyse how the coolant and solid interact with changes to the coolant jacket design. By using CHT, the temperature eld within both the coolant and solid regions can be simulated within a common model. In this master thesis, a parameter sensitivity analysis has been performed on a cylinder head of a SI engine using a 3D-CHT-CFD model. The analysis investigate how coolant mass ow, coolant pressure/saturation temperature, thermal conductivity, coolant jacket displacement and surface topology a ect the heat transfer within the cylinder head. Temperature elds on both the coolant jacket walls and the gas/solid interfaces are analysed, as well as the wall boiling heat ux calculated using a correlation proposed by W.M. Rohsenow [1]. The analysis has also compared local static pressure dependent saturation temperatures of the coolant with constant saturation temperature. For the geometrical parameters, further analysis is needed to draw conclusions on the e ect of structure durability as well as heat transfer and boiling.
Keywords: Strömningsmekanik och akustik; Hållbar utveckling; Transport; Fluid Mechanics and Acoustics; Sustainable Development; Transport